Seismostratigraphic signature of the Western Antarctic Ice Sheet advance during the Late Quaternary on the Little America BAsin, Eastern Ross Sea, Antarctica - CORRADI, NICOLA; IVALDI, ROBERTA; PITTA', ANTONELLA; Finocchiaro, F. (Alfred-Wegener-Stiftung, 2003)
The Little America Basin (LAB), the easternmost basin of the Ross Sea, is a difficult area to access due to its sea ice cover. Even if there are models of the Late Quaternary evolution of the West Antarctic Ice Sheet (WAIS) that include this sector, the available data regarding the high- and very high-resolution seismic profiles and sampling are quantitatively inferior to those of other sectors of the Ross Sea. The seismic surveys (Sparker 400 J and Sub Bottom Profiler 3.5 kHz) and the preliminary data on the sediments (magnetic susceptibility) have permitted us to better define the evolution of the sheet in this sector. Seismic data highlighted differences between the geometry of the deposits along the eastern and western flanks, and differences of internal structure in the northern and southern part of the basin. Seismic lines in the southern sector of the LAB show deposits as glacial till tongues, especially on the western flank, and several unconformities sub-outcropping under thin glacialmarine cover on the eastern flank. The northern sector shows several unconformities and glacial till tongues on the western flank; the outer shelf in this part is characterized by residual glacialmarine deposits. A dip-oriented seismic profile shows a sedimentary ridge that divides the basin into two sectors, which could be interpreted on geomorphic features and seismic stratigraphy as a grounding zone wedge (Anderson, 1999). On the outer shelf we recognized an analogous ridge with structures, internal geometry and sedimentary characteristics that could be referred to a more ancient cycle grounding line. Magnetic susceptibility data confirm the differences between the northern and the southern sectors of the basin and show the increase of diatomaceous sediments (even with glacialmarine compound) to the south.